2007
DOI: 10.4049/jimmunol.178.9.5659
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin-Independent Expression of TNF-Related Activation-Induced Cytokine by Stromal Cells in Cryptopatches, Isolated Lymphoid Follicles, and Peyer’s Patches

Abstract: Stromal cells play a crucial role in the organogenesis of lymphoid tissues. We previously identified VCAM-1+ stromal cells in cryptopatches (CP) and isolated lymphoid follicles (ILF) in the small intestine of C57BL/6 mice. Nonhemopoietic stromal cell networks in CP and ILF of adult mice also expressed FDC-M1, CD157 (BP-3), and TNF-related activation-induced cytokine (TRANCE). Individual stromal cells were heterogeneous in their expression of these markers, with not all stromal cells expressing the entire set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 49 publications
3
56
1
2
Order By: Relevance
“…7,[12][13][14] We have previously shown that RANKL is expressed on stromal cells found throughout CPs, but is preferentially expressed by stromal cells located in the subepithelial dome of ILFs and PPs. 15 We also showed RANKL appears on stromal cells later in ontogeny than other stromal cell antigens including the follicular dendritic cell marker FDC-M1, vascular cell adhesion molecule 1 (VCAM-1), and CD157, and can still be induced when LT␣ 1 ␤ 2 signaling through the LT␤R is blocked. In this study, we used RANKL Ϫ/Ϫ mice to further investigate the role of RANKL in the development of CPs and ILFs, and found that in the absence of RANKL small intestinal, but not colonic, CPs fail to express CXCL13, recruit B cells, or develop into ILFs.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…7,[12][13][14] We have previously shown that RANKL is expressed on stromal cells found throughout CPs, but is preferentially expressed by stromal cells located in the subepithelial dome of ILFs and PPs. 15 We also showed RANKL appears on stromal cells later in ontogeny than other stromal cell antigens including the follicular dendritic cell marker FDC-M1, vascular cell adhesion molecule 1 (VCAM-1), and CD157, and can still be induced when LT␣ 1 ␤ 2 signaling through the LT␤R is blocked. In this study, we used RANKL Ϫ/Ϫ mice to further investigate the role of RANKL in the development of CPs and ILFs, and found that in the absence of RANKL small intestinal, but not colonic, CPs fail to express CXCL13, recruit B cells, or develop into ILFs.…”
mentioning
confidence: 62%
“…15 In previous studies, we showed that aly/aly mice lacking functional NF-B-inducing kinase (NIK) or wild-type mice in which LT␣ 1 ␤ 2 signaling was blocked with LT␤R-Ig also had defective stromal antigen expression in CPs, failing to express VCAM-1, CD157, and FDC-M1, but retaining RANKL expression. The CPs from the aly/aly mice also failed to develop into ILFs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations